Ischemia modified albumin among type 2 diabetic patients visiting a tertiary care center of Kathmandu - Thapa, Sangita; Rayamajhi, Rabindra Jang; Gautam, Surakshya; Dahal, Sirjana (Journal of Chitwan Medical College, 2020)
Background: Chronic hyperglycemia in diabetes may increase oxidative stress causing ischemia and long-term complications of diabetes. It may also alter albumin, increasing the concentration of serum ischemia modified albumin. The present study was conducted to estimate serum ischemia modified albumin level and to assess its relationship with parameters of glycemic control in diabetic patients. Methods: In this study, 130 type 2 diabetic patients were enrolled and blood samples were analyzed for ischemia modified albumin, glycated hemoglobin, fasting and postprandial blood glucose. Parameters of glycemic control were estimated using routine standard methods and serum ischemia modified albumin was measured manually by spectrophotometric cobalt-albumin binding assay. Participants with glycated hemoglobin level less than 7% were labeled as group 1 and participants with glycated hemoglobin value more than or equal to 7% were labeled as group 2. Results: Group 2 participants had significantly higher mean serum ischemia modified albumin as compared to group 1 (p<0.001). There was significant positive correlation between ischemia modified albumin and parameters of glycemic control; glycated hemoglobin (r=0.300, p=0.001), fasting blood glucose (r=0.239, p=0.006), postprandial blood glucose (r=0.318, p<0.001). However the relationship of ischemia modified albumin with age, body mass index and duration of diabetes were statistically insignificant. Conclusions: The present study shows increase in serum ischemia modified albumin with increase in all three glycemic parameters. This finding suggests that ischemia modified albumin can be used as a marker of hyperglycemia induced oxidative stress in diabetes.